Evaluasi Pemenuhan Hak Atas Kesehatan bagi Masyarakat Miskin di Provinsi Nusa Tenggara Barat - Firdaus, Firdaus (Jurnal HAM, 2010)
The evaluation discusses the implementation by the Guidelines for the Community Health Insurance Year 2008, the health insurance for the poor has become reality. JAMKESNAS is a great agenda for realizing to fulfill the rights of health that is facilitated by the Ministry of Health and Local Government with funding sourced from the tax and the natural resources. The core issues are implementation and realization JAMKESMAS programs such as, basic health services and referrall health service, beside to show the response of  poor society. This evaluation used qualitative methods with combine between juridical normative approach to review the legal and regulatory norms as well as policy analysis and implementation of study related any policy issued by the  local government to fulfill rights of health for the poor. The result of evaluation show relatively successfully help poor communities in the province West of Nusa Tenggara to get free service of health in the context of human rights protection from the state, but still need more significant enhancements for optimal benefits. There are several problems that needs the way out such as : the distribution of cards is not on target; variety of drugs and patients’ needs. The limited-quality drugs to be a dilemma for Hospital in Mataram.